Martí: Nation, subject and identity upon rereading Nuestra América (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
In the current climate of pressing questions about regional identity, there tends to be, if not ahistorical or essentialist versions, at least determinist or simplistic ones that only reduce the notion cornering it into categories that contribute little or nothing to the understanding of our peoples. Therefore, it is pertinent to turn our eyes toward a vision of identity that should be conceived as a complex, conflictive, and relational socialphenomena in constant reconstruction. “Nuestra América”, in this sense, continues to be a fundamental text since it not only permits us to understand the idea of the modern nation proposed by the Cuban, but also the way in which it must be build. This is an inconclusive sociocultural project which will only be finished if difference is accepted as a basic building block of our heterogenous reality.
Keywords: Nation; Subject; Cultur; Identity; Latin America; José Martí